Mechanical Properties of Concrete incorporating natural Pozzolanic Material Subjected to Crude Oil - Hama, Shaho (Iraqi Journal of Civil Engineering, 2018)
The paper shows the final findings of the effect of metakaolin on the strengths properties of concrete exposed to crude oil. Sulfate resistance Portland cement of V type was used and specimens of concrete were adjusted and subjected to a solution of concentrated crude oil. However, the samples are cured in a control media at immersion ages of (28, 56 & 120 days) with ambient temperature, then samples have been kept in curing water for comparisons purpose as well. The results explain that the use of metakaolin reinforces compressive, flexural and splitting resistance of concrete which is exposed to crude oil. The compressive strength reduction increased from 8.0% at (28 days) to 37.7% at (120 days) curing for normal weight concrete (NW) whereas the concrete incorporating metakaolin (MC) has a reduction of 6.0% at (28 days) & 29.3% at (120 days). .